Zebrafish (Danio rerio) physiological and behavioural responses to insect-based diets: a multidisciplinary approach - Zarantoniello, Matteo (Sci Rep, 2020)
Black Soldier Fly (BSF) meal is considered as an alternative, emerging and sustainable ingredient for aquafeed production. However, results on fish physiological responses are still fragmentary and often controversial, while no studies are available on fish behavior in response to these new diets. The present work represents the first comprehensive multidisciplinary study aimed to investigate zebrafish physiological and behavioural responses to BSF-based diets. Five experimental diets characterized by increasing inclusion levels (0, 25, 50, 75 and 100% respect to fish meal) of full fat BSF prepupae meal were tested during a 2-months feeding trial. Prepupae were cultured on coffee silverskin growth substrate enriched with a 10% Schizochytrium sp. to improve insects’ fatty acids profile. The responses of zebrafish were assayed through biometric, histological, gas chromatographic, microbiological, spectroscopic, molecular and behavioural analyses. Results evidenced that BSF-based diets affected fish fatty acid composition, while behavioural tests did not show differences among groups. Specifically, a 50% BSF inclusion level diet represented the best compromise between ingredient sustainability and proper fish growth and welfare. Fish fed with higher BSF inclusions (75 and 100%) showed hepatic steatosis, microbiota modification, higher lipid content, fatty acid modification and higher expression of immune response markers.